THE COACHING SYSTEM FOR FOOTBALL ATHLETES AT FLOBAMORATA STATE HIGH SCHOOL FOR SPORTS TALENTS IN KUPANG IN MAINTAINING SPORTSMANSHIP - lodalaleng, damasus (Postgraduate School, Universitas Nusa Cendana, 2024)
This paper provides information about the coaching system for football athletes at Flobamorata State High School for Sports Talents in Kupang in maintaining sportsmanship during matches. The coaching system is implemented at the school, dormitory, and training grounds. The research uses a qualitative method, employing triangulation techniques through participatory observation, interviews, and documentation studies. The sample sources were determined purposively and through snowball sampling, including the principal, student affairs coordinator, curriculum coordinator, dormitory manager, coaches, and football athletes. Data were analyzed using the Miles and Huberman narrative descriptive method. Based on the research results, the implementation of the coaching system at the school, dormitory, and training grounds in various ways helps to develop the character of SKO NTT football athletes to maintain sportsmanship during matches. The research found that physical strength, character, and psychology can influence a football athlete’s sportsmanship during matches.